Novel Ultrasound Liver Attenuation Imaging for Detection of Liver Steatosis: Comparison with MRI Based Imaging Methods with Liver Biopsy as A Reference Standard - Chiyanika, Chileka; Liu, Kin Hung; Wong, Vincent Wai-Sun; Chu, Winnie Chiu Wing (Archives of Clinical and Biomedical Research, 2023)
Background and aim: Non-alcoholic fatty liver disease is a predominant cause of chronic liver disease worldwide. The aim of this study was to evaluate the performance of the novel ultrasound attenuation imaging (ATI) with MRI-proton density fat fraction (PDFF) and proton magnetic resonance spectroscopy (proton-MRS) in detecting and grading of liver steatosis, using liver biopsy as a reference standard. Materials and methods: From March 2019 to September 2021, 15 adult subjects (age: 38 years, Male/female:5/10 females, BMI: 38.5kg/m2) with morbid obesity planned for laparoscopic-sleeve-gastrectomy were recruited, and an intraoperative liver biopsy was performed. A control group of 8 healthy lean subjects (age: 25 years, Male/female: 4/4 females, BMI: 20.2kg/m2) was also enrolled. ATI, MRI-PDFF, and proton-MRS were performed on the same day and within two weeks before surgery. Results: Liver steatosis was present in 100% of the patients. ATI correlated with steatosis grade (r=0.833, p< 0.001). MRI-PDFF correlated with steatosis grade (r=0.926, p< 0.001) and non-alcoholic steatohepatitis activity score (r=0.820, p=0.001). ATI correlated with MRI-PDFF (r=0.885, p<0.001). AUROCs of ATI were 0.91, 0.97, and 0.93 for detecting steatosis grades 1,2, and 3 respectively. Conclusions: ATI showed no significant difference in the diagnostic performance when compared to MRI-PDFF and proton-MRS.